The Critique of Pure Reason - Kant, Immanuel, 1724-1804; Meiklejohn, J. M. D. (John Miller Dow), 1830-1902 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Critique of Pure Reason" by Immanuel Kant is a philosophical work published in 1781. Kant investigates the limits and scope of metaphysics, asking how we can know anything before experiencing it. He challenges both rationalist and empiricist traditions, introducing revolutionary ideas about space, time, and knowledge. The central question driving the work is: "How are synthetic a priori judgments possible?" Kant argues this matter is crucial to the survival of human reason itself. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Critique_of_Pure_Reason
Release date is 2003-07-01
Charles Aldarondo and David Widger
Keywords: Knowledge, Theory of; Causation; Reason; Philosophy, German